2012
DOI: 10.4236/ait.2012.22003
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Low-Power Active RFID for Container Tracking at 2.4 GHz Frequency

Abstract: In this paper a new active RFID system at 2.45 GHz based on the low-power system-on-chip CC2530 RF transceiver is designed and implemented. Only by using of an integrated multi-channel fast chip, both the MCU and RF operations are done which makes the RFID more reliable and reduces the complexity of the hardware and cost, vividly. This RFID system utilizes the Zig-Bee IEEE 802.15.4 standard in the ISM band. A lot amount of energy is restored by setting Tags in the sleep mode in the most of times. The maximum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It found that Wi-Fi, visualization, WSN, Bluetooth and RFID were ranked high. This is because they are reliable and easy to control, which correspond to Moeinfar et al (2012), which states that it is more reliable, efficient, secure, inexpensive and accurate. RFID has an extensive range of wireless applications such as distribution, tracing and patient monitoring.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It found that Wi-Fi, visualization, WSN, Bluetooth and RFID were ranked high. This is because they are reliable and easy to control, which correspond to Moeinfar et al (2012), which states that it is more reliable, efficient, secure, inexpensive and accurate. RFID has an extensive range of wireless applications such as distribution, tracing and patient monitoring.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…RFID has an extensive range of wireless applications such as distribution, tracing, patient monitoring, military apps etc. [21].…”
Section: Radio Frequency Identification (Rfid)mentioning
confidence: 99%
“…In the network under study, while the tags are battery-free and cannot generate active radio signals, the channel state information (CSI) can be acquired at the tag reader through semi-blind channel estimation [19] or blind channel estimation [20]. As for the control signaling, following the similar procedure developed in [21], the reader allocates an identification (ID) number to each tag, and then, if necessary, wakes up the desired one by its unique ID and communicates with it by using the RF signals from the AP. As passive tags are usually equipped with low-power oscillators, in practice, the EPC Gen2 protocol [22] uses slotted Aloha to synchronize the AP and all tags in a cell.…”
Section: B Signal Modelingmentioning
confidence: 99%